The Concept of Loving One Another in the Perspective of the Hadith: Study of Takhrij - Wahid, Mohamad Audi Al-Amin bin Amin; Rifa'i, Ahmad (Journal of Takhrij Al-Hadith, 2024)
This study aims to discuss the hadith about the concept of mutual love between others. This research uses a qualitative approach by applying descriptive-analytical methods. The formal object of this research is the science of hadith, while the material object is the concept of mutual love between others in the narration of Bukhari No. 6828. The results and discussion of this research show that the status of hadith quality hasan li ghairihi with the qualifications of maqbul ma'mul bih for the practice of Islam in grounding affection between others. This study concludes that the hadith narrated by Imam Bukhari No. 6828 is relevant to be used as inspiration in doing good to others so that what is created is only kindness, which comes from love and compassion.